Associations of metal mixtures with metabolic-associated fatty liver disease and non-alcoholic fatty liver disease: NHANES 2003–2018 - Xie, Zhilan; Aimuzi, Ruxianguli; Si, Mingyu; Qu, Yimin; Jiang, Yu (Frontiers in Public Health, 2023)
Objective: The hepatotoxicity of exposure to a single heavy metal has been examined in previous studies. However, there is limited evidence on the association between heavy metals mixture and nonalcoholic fatty liver disease (NAFLD) and metabolic-associated fatty liver disease (MAFLD). This study aims to investigate the associations of 13 urinary metals, individually and jointly, with NAFLD, MAFLD, and MAFLD components. Methods: This study included 5548 adults from the National Health and Nutrition Examination Survey (NHANES) 2003-2018. Binary logistic regression was used to explore the associations between individual metal exposures and MAFLD, NAFLD, and MAFLD components. Bayesian kernel machine regression (BKMR) and Quantile-based g-computation (QGC) were used to investigate the association of metal mixture exposure with these outcomes. Results: In single metal analysis, increased levels of arsenic (OR 1.09 [95%CI 1.03-1.16]), dimethylarsinic acid (1.17 [95%CI 1.07-1.27]), barium (1.22 [95%CI 1.14-1.30]), cobalt (1.22 [95%CI 1.11-1.34]), cesium (1.35 [95%CI 1.18-1.54]), molybdenum (1.45 [95%CI 1.30-1.62]), antimony (1.18 [95%CI 1.08-1.29]), thallium (1.49 [95%CI 1.33-1.67]), and tungsten (1.23 [95%CI 1.15-1.32]) were significantly associated with MAFLD risk after adjusting for potential covariates. The results for NAFLD were similar to those for MAFLD, except for arsenic, which was insignificantly associated with NAFLD. In mixture analysis, the overall metal mixture was positively associated with MAFLD, NAFLD, and MAFLD components, including obesity/overweight, diabetes, and metabolic dysfunction. In both BKMR and QGC models, thallium, molybdenum, tungsten, and barium mainly contributed to the positive association with MAFLD. Conclusion: Our study indicated that exposure to heavy metals, individually or cumulatively, was positively associated with NAFLD, MAFLD, and MAFLD components, including obesity/overweight, diabetes, and metabolic dysfunction. Additional research is needed to validate these findings in longitudinal settings.